Suitability of the porcine aortic model for transcatheter aortic root repair. (2nd February 2018) - Wang, Changtian; Lachat, Mario; Regar, Evelyn; von Segesser, Ludwig Karl; Maisano, Francesco; Ferrari, Enrico
Abstract: OBJECTIVES: To treat aortic valve disease and concomitant root disease with transcatheter techniques, 'composite graft' implants are required. Our goal was to assess the suitability of the porcine aortic root for transcatheter root repair tests. METHODS: Eight pig hearts explanted from domestic pigs used in experimental surgery were compared to data from the literature on human hearts. The measured diameters included those of the annulus, sinuses of Valsalva, coronary ostia, sinotubular junction, ascending aorta, innominate artery and aortic arch. The measured distances were from the coronary ostia to the nadir of the corresponding annulus; from the innominate artery to the nadir of the corresponding annulus; from the small curvature of the arch to the nadir of the corresponding annulus. RESULTS: The mean weight of the pigs was 89 ± 5.4 kg. The mean aortic annulus diameter was 20 ± 1.2 mm (human: 23.0 ± 2.5 mm), the sinus of Valsalva diameter was 20.5 ± 0.5 mm (human: 31.4 ± 3.4 mm) and the sinotubular junction diameter was 20 ± 0.9 mm (human: 27.2 ± 3.0 mm). The diameter of the mean ascending aorta was 19 ± 0.7 mm (human: 29.3 ± 4 mm); the diameter of the innominate artery was 8.5 ± 0.7 mm, that of the aortic arch was 15 ± 0.7 mm and that of the coronary ostia was 5 ± 0.5 mm (left) and 4.7 ± 0.5 mm (right) (human: 4.8 ± 0.5 mm and 3.7 ± 0.9 mm). The distances from the left and right coronary orifices to the corresponding annuli were 8 ± 1.5 mm and 14 ± 2.4 mm, respectively (human: 14.7 ± 1.3 mm; 15.4 ± 1.7 mm). The distances from the innominate artery to the nadirs of the left and right coronary annuli were 44 ± 4.3 mm and 41 ± 4 mm (human: 80 ± 17 mm). The distance from the curvature of the small arch to the annulus was 35 ± 4.9 mm. CONCLUSIONS: The porcine heart can be used as an experimental model to design and test new devices for catheter-based composite repair of the aortic root. Nevertheless, caution is required in using devices with tailored dimensions that must be adapted to the smaller pig's root.